2013
DOI: 10.1039/c3cc42779j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and sonication-induced assembly of Si-DDR particles for close-packed oriented layers

Abstract: Here, we report a seeded growth protocol for synthesizing monodisperse Si-DDR particles of ~1.3-10 μm by varying the seed amount. These Si-DDR particles were deposited onto porous α-Al2O3 discs via sonication-induced assembly, constituting close-packed h0h-oriented layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The width of the cracks ranged from 50 nm to 200 nm that explains the predominant Knudsen diffusion gas transport behavior. Kim et al [10] observed very similar cracks formed in α-alumina supported pure-silica DDR membranes, which likely caused the membrane's poor gas permselectivity. In the current membrane, the inclusion of the Sigma-1 seeds in the zeolite layer might also have played a role in crack development during the thermal treatment that needs to be further investigated in the future.…”
Section: Membrane Modification and Single Gas Permeationmentioning
confidence: 95%
See 2 more Smart Citations
“…The width of the cracks ranged from 50 nm to 200 nm that explains the predominant Knudsen diffusion gas transport behavior. Kim et al [10] observed very similar cracks formed in α-alumina supported pure-silica DDR membranes, which likely caused the membrane's poor gas permselectivity. In the current membrane, the inclusion of the Sigma-1 seeds in the zeolite layer might also have played a role in crack development during the thermal treatment that needs to be further investigated in the future.…”
Section: Membrane Modification and Single Gas Permeationmentioning
confidence: 95%
“…Kim et al used the DDR-seeded secondary growth method to synthesize DDR membrane and the membrane exhibited no permeation selectivity between CO 2 and N 2 (i.e. selectivity ~ 1) [10] which differs qualitatively from the values of >10, which were experimentally obtained by Tomita et al [1] and theoretically predicted by Krishna et al [7]. Bose et al synthesized DDR membrane by sonication mediated hydrothermal reaction [11].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Kim et al prepared Si-DDR particles of 1.3~10 mm by varying the seed amount. These Si-DDR particles were deposited onto porous a-Al 2 O 3 discs via sonicationinduced assembly, constituting close packed h0h-oriented layers [31].…”
Section: Introductionmentioning
confidence: 99%
“…Although alternative synthesis approaches for DDR zeolites have been proposed to reduce the reaction time and simplify the synthetic conditions, other zeolite phases such as sigma‐2 (SGT) or dodecasil 1 hexagonal (DOH) are often uncontrollably co‐synthesized, arising from the use of the same structure directing agent (1‐adamantylamine) . In addition, the particle size of DDR zeolites has a wide distribution so that it is quite difficult to produce a uniform seed layer, which is critical for the formation of a continuous membrane by epitaxial growth of seeds . Thus, the formation of continuous membranes based on the secondary growth methodology is inhibited.…”
Section: Introductionmentioning
confidence: 99%